Teacher–child relationships in the context of poverty: the role of frequent school mobility. Issue 1 (2nd January 2018) - McKinnon, Rachel D.; Friedman-Krauss, Allison; Roy, Amanda L.; Raver, C. Cybele
ABSTRACT: Children's relationships with their teachers are critical for classroom-based learning, but children growing up in poverty may be at risk for lower-quality relationships with teachers. Little is known about how changing schools, one poverty-related risk, affects teacher–child relationships. Using growth curve models that control for a host of other poverty-related risks, this study explores the association between children changing schools frequently (defined as three or more school moves) between preschool and third grade and the quality of their relationships with their teachers over these five years in a low-income, ethnic-minority sample. Children who frequently moved schools were reported to be less close to their teachers in third grade and experienced steeper declines in closeness than children who did not change schools frequently. Moreover, the effects of frequent school mobility at third grade were robust to other poverty-related risks, including residential mobility, parental education risk, family income, and single-parent households. Changing schools was unrelated to children's conflict with teachers. We discuss these findings in the context of policies that support students' transitions when changing schools.